Differences over Marital Adjustment of Living Apart Together Couples and Proximal Couples - Johari, Shikha; Singh, Ritu; Mehra, Manisha (Indian Journal of Extension Education, 2020)
Many couples are unable to envision the kind of adjustments required to transition smoothly from one phase of the marital relationship to another. The expectations from marital life are often skewed leading to disappointments. Thus, for a fulfilling relationship, the couples have to develop abilities to anticipate potholes and make adjustments readily. Marital adjustment of every couple is unique and like any other domain of adjustment it too is defined by childhood experiences, family type, family structure etc. The present study aimed at assessing and comparing the similarities and differences in marital adjustment across new form of family, that is, living apart together couple families (LATC) and proximal couple families (PC). Dyadic Adjustment tool was administered to 75 living apart together couples and 75 proximal couples drawn through snowball sampling from Distt. U.S. Nagar of Uttarakhand. Both, husband and wife’s responses on marital adjustment were recorded using mixed methods of data collection namely mailed questionnaire, face to face and telephonic interviews. Statistical analysis of the data showed that living apart together couples practiced significantly higher affectional expression than proximal couples. Both forms of couples were seen to be statistically similar on dyadic consensus, cohesion and satisfaction. Hence, proximal and long distance marital relationships have their own pros and cons, however, it entirely depends on couples how they convert cons into pros.
Keywords: Commuter couple; Compatibility; Distant relationship; Dyadic adjustment; Proximity